Assessment and Risk Identification of Water Resources Carrying Capacity in the Pearl River Basin - ZHOU Xuexin; LUO Hao (Renmin Zhujiang)
:Taking the Pearl River Basin as the research object,this paper builds an evaluation index system for water resources carrying capacity with 13 indexes selected from four aspects of water resources,society,economy,and the ecological environment by using the data in the water resources bulletin and statistical yearbook of the year 2018.The technique for order of preference by similarity to ideal solution (TOPSIS) model integrated with combined weighting is used to evaluate and analyze the water resources carrying capacity of 46 cities in the basin.The hot spot analysis method is employed to identify the high-risk areas of water resources carrying capacity there.The results show that the overall water resources carrying index of the basin is 0.504,and the water resources carrying capacity is at Level 2,reflecting the moderate overall water resources carrying status of the basin.There are significant differences in water resources carrying capacity among different regions in the basin.On the whole,the middle-upper reaches of the basin have better carrying capacity than the upper and middle-lower reaches.The Pearl River Delta region is facing great water resources carrying capacity pressure.The distribution of water resources carrying capacity is highly concentrated in the basin.The risk of water resources carrying capacity is not significant in most regions of the basin.Five cities,including Shenzhen,Dongguan,Guangzhou,Foshan,and Zhongshan,are in the hot spot range (99% confidence level).They are high-risk areas of water resources carrying capacity,all concentrated in the Pearl River Delta region.